A Discussion on Interdisciplinary Approach of Visual Art Syllabus in Malaysian Higher Education - Mohamad Faizuan Mat; Sarah Naemah Aman Leong; Nourah Nasser Al-Nahari (Journal of Visual Art and Design, 2023)
This article contributes to the discussion on the need to adopt an interdisciplinary approach in the visual art syllabus, specifically in higher education in Malaysia. Over the last two decades, the academic world has faced rapidly advancing technology and the rise of Industrial Revolution 4.0 (IR4.0). Because of the increased level of high-tech software and hardware competency among students, universities are in dire need to improve and innovate their current syllabi. Hence, this study was carried out to discuss the need to adopt an interdisciplinary approach to improve current visual art syllabi in Malaysia. The topics that are explored in this paper include the definition of an interdisciplinary approach in visual art syllabi, the current status of visual art syllabi in Malaysia, factors that are important for the integration of art with other fields, and how an interdisciplinary approach can be implemented. The data used in this research were obtained from a seminar, in-depth interviews, and a literature review, and were analyzed using a qualitative method. The findings indicate that visual art education duly needs a new program or needs to be revamped into a future-ready curriculum. Therefore, an interdisciplinary approach, or the integration of two bodies of knowledge in one program, could be one of the solutions to this issue.